The Islamic Threat: Myth or Reality? By John L Esposito. New York: Oxford University Press, 1992, ix + 243 pp. (American Journal of Islam and Society, 1993)
There is little dispute that the Iranian revolution, the ensuing hostagecrises in Tehmn and Beirut, the Salman Rushdie affair, and, finally, thePemian Gulf war have drastically changed the image of Islam in the West.The hetoric of the most ardent Muslim activists has been accepted at facevalue, and Islam has been identified as a revolutionary force with an axe togrind against the West. Although the Western phobia of Islam has somejustification, the West has allowed stereotypes and shibboleths to rule itsjudgment too easily. Explicitly, as well as implicitly, Islam is depicted in themedia and even academic literature as the religion of war, vengeance, anddestruction-as a force that is inimical to the orderly conduct of internationalrelations and the progress of society and politics. Islam is viewed as hostileto democracy, minority rights, and women's welfare. Islam as a world civilizationhas been reduced to Islamic fundamentalism, and even then the Westhas preferred to cling to political slogans rather than grapple with complexsociopolitical pmesses in undetstanding the theoretical and political challengeof Islamic movements.The radications of the simultaneous reduction of Islam to fundamentalismand the "mythologization" of fundamentalism are immediately clear.The West turned a blind eye to a brutal military coup in Algeria in 1991, believingthat martial rule would be a far better option for Algeria and the Westthan an Islamic government in Algiers. The reaction to the crisis in the formerrepublics of Yugoslavia has been equally perplexing, especially in the lightof Serbia's glorification of its genocidal carnage of Bosnians as "a worthycause" that Europe will eventually appreciate. After all, the Serbs are "doingEurope a favor by ridding it of the menace of Islam." Muslims have in factcharged, and rightly so, that the West follows a different set of standards ondemocracy and human rights when it comes to Muslim societies.Is the Western reaction to things Islamic mere genuflection or does it reveala more deep-seated anger and distrust of Islam? If the latter is the case,what will the consequences of such a policy be for global interests of theWest? The Islamic threat: Myth or Reality? offers answers to these queries.Esposito, a leading expert on Islamic studies who has written prolifically onthe relation of Islam to politics, provides a lucid examination of the roots ofMuslims' activism and the Westem response to it. He places the attitude ofIslamic movements towards the West in the context of the Muslim experience ...